ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PREVALENSI KETIDAKCUKUPAN KONSUMSI PANGAN DI SUMATERA BARAT MENGGUNAKAN GEODA - Eri Mardison (Poltekkes Kemenkes Semarang, 2020)
Background: Daily energy requirements must be fulfilled for a healthy and active life. Prevalence of Undernourishment (PoU) is an indicator which are developed for goal. A number of factors were expected affecting PoU were tested in this study. We also tested the possibility of these factors could have a spatial correlationObjectives: The study produced a map of the spread of PoU and the factors which were influenced them (independent variables). The study need to yield the best estimation model.Method : This study produce spread map of all variables, for visible purposes, and the classical regression were made. All OLS assumption will be test. Then, SAR and SEM models will be made. Finally, the best model for this study will be chosen. GeoDa software helps all steps.Results : This study concludes PoU has positive auto correlation and growth has a negative autocorrelation. The best model which produced is the Spatial Error Model (SEM). The slow trend of PoU in West Sumatera Barat is strongly suspected due to the habit of West Sumatera residents in consuming high-calorie foods such as rendang, curry and coconut milk.